PATTERNS OF SILVER NANOPARTICLES CONCENTRATION SYNTHESIS - Anastasia A. Blinova; Andrey V. Blinov; Alezander V. Serov; Andrey G. Khramtsov (Вестник Северо-Кавказского федерального университета, 2022)
The article provides a view on a synthesis of the substance based on silver nanoparticles; there was also optimization of the synthesis process, with data obtained that describe the impact of various factors on silver nanoparticles synthesis